1999
DOI: 10.1002/(sici)1097-0231(19990930)13:18<1850::aid-rcm728>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Collisional stabilization of negative ions produced by a monoenergetic electron beam

Abstract: The effect of different buffer gases on the intensity of negative ions was studied using a gas chromatography/electron monochromator mass spectrometer (GC/EM-MS). The buffer gas was introduced into the ion source not to moderate the electron energies, but specifically to investigate the process of collisional stabilization of negative ions. Three different designs of ion source were tested to study this phenomenon. It was found that collisional stabilization has a profound effect on the intensity of molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Berkout et al investigated the use of buffer gases for additional ion stabilization in EM‐MS to increase sensitivity (Berkout, Mazurkiewicz, & Deinzer, ). Electron energy was scanned from 0 to 10 eV in 0.1–0.2 sec on a quadrupole GC/EM‐MS, and helium was used as a buffer gas at pressures from 0.5 to 12 mTorr.…”
Section: Research At Oregon State University Prior To Commercializationmentioning
confidence: 99%
“…Berkout et al investigated the use of buffer gases for additional ion stabilization in EM‐MS to increase sensitivity (Berkout, Mazurkiewicz, & Deinzer, ). Electron energy was scanned from 0 to 10 eV in 0.1–0.2 sec on a quadrupole GC/EM‐MS, and helium was used as a buffer gas at pressures from 0.5 to 12 mTorr.…”
Section: Research At Oregon State University Prior To Commercializationmentioning
confidence: 99%
“…This excess internal energy is large enough in most cases to cause autodetachment following first-order kinetics with a rate constant, k 2 . In the presence of a buffer gas B, however, the excited molecular radical anion may loose its excess internal energy by collision and thus lead to a stabilized thermal-energy molecular radical anion with second order kinetics according to rate constant k 3 [6,8]. The reverse reaction is only of minor importance, except for compounds with very low EA.…”
Section: Resonance Electron Capture (Rec)mentioning
confidence: 99%
“…Use of electron monochromators circumvents the need for high buffer-gas pressure (~ 1 Torr) to thermalise electrons, but recent studies have demonstrated the beneficial effects of a buffer gas at low pressure (10 mTorr) on collisional cooling of the excited molecular anion [8].…”
Section: Electron Monochromatorsmentioning
confidence: 99%
“…On the other hand, using the highly fluorinated derivatives, negative ion chemical ionisation (NICI) can also be applied . Basically, resonance electron capture (REC) and dissociative REC are the mechanisms involved, where REC produces a molecular radical anion in its excited state that must be stabilised to prevent electron autodetachment, whereas dissociative REC results in non‐radical anions with a distribution of internal energies, depending largely on the leaving group and its ability to absorb excess internal energy, which increases with its size . The REC process also adds another dimension of selectivity to the analytical process as it strongly depends on the electron affinity of the target molecule, and thus on its electronegativity, rendering it as electrophoric.…”
mentioning
confidence: 99%